Brysonville Schoolhouse Revisited: A Rural Open-Mic Responds to a Pandemic–An Interview with Bruce Barr and Alison Boyle - Patterson, Glenn (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
In this edited interview, Glenn Patterson speaks with Bruce Barr and Alison Boyle of Quebec's Chateauguay Valley to discuss their initiative to transition Brysonville Schoolhouse Revisited, a monthly open mic, to an online livestream format using Zoom and Facebook Live. They describe their personal motivations for making this transition, how it impacted their daily lives and weekly schedules in the first months of the pandemic, and their experiences as non-experts working with these popular technologies. They also point out some of the principal barriers facing ageing and rural communities wishing to transition to online performance spaces and contemplate the prospects for the future of the event.